Knockout of Zeb2 ameliorates progression of renal tubulointerstitial fibrosis in a mouse model of renal ischemia–reperfusion injury. Issue 3 (1st November 2021) - Inotani, Satoshi; Taniguchi, Yoshinori; Nakamura, Keisyun; Nishikawa, Hirofumi; Matsumoto, Tatsuki; Horino, Taro; Fujimoto, Shimpei; Sano, Shigetoshi; Yanagita, Motoko; Terada, Yoshio
ABSTRACT: Background: Zeb2, a zinc finger E-box-binding homeobox transcription factor, regulates transforming growth factor (TGF)- β signaling pathway. However, its role in the pathogenesis of acute kidney injury (AKI) and AKI-to-chronic kidney disease (CKD) transition is unclear. Methods: We evaluated Zeb2 function in a bilateral renal ischemia–reperfusion injury (IRI)-induced AKI model using proximal tubule-specific Zeb2 conditional knockout (Zeb2-cKO) and wild-type (WT) mice, and in renal biopsy samples. Results: In Zeb2-cKO mice, the levels of plasma creatinine and blood urea nitrogen post-IRI were significantly lower than that in WT mice. Immunohistological analysis revealed mild tubular injury, reduced neutrophil infiltration, fewer fibrotic changes and reduced expression of fibrotic proteins [collagen type IV, α -smooth muscle actin ( α -SMA), fibronectin and connective tissue growth factor (CTGF)], at 3–14 days post-IRI. Zeb2 expression was upregulated in proximal tubular cells post-IRI in WT mice. Zeb2 siRNA transfection reduced TGF- β -stimulated mRNA and protein expression of collagen type IV, α -SMA, fibronectin and CTGF in cultured renal tubular cells. Patients with AKI-to-CKD transition exhibited high Zeb2 expression in renal tubules, as revealed by renal biopsy. Hypoxia and CoCl2 -treatment upregulated Zeb2 promoter activity and mRNA and protein expression in cultured renal tubular epithelial cells, suggesting a regulatory role for hypoxia. Conclusions: Zeb2 was upregulated in renal tissues in both mice and humans with AKI. Zeb2 regulates fibrotic pathways in the pathogenesis of AKI and AKI-to-CKD transition. Therefore, inhibition of Zeb2 could be a potential therapeutic strategy for AKI.